Proceedings of the International Colloquium in Textile Engineering, Fashion, Apparel and Design 2014 (ICTEFAD 2014) 2014
DOI: 10.1007/978-981-287-011-7_5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fabric Weave on the Tensile Strength of Woven Kenaf Reinforced Unsaturated Polyester Composite

Abstract: Abstract-Natural fibers have gained attention in composite making since it is sustainable, renewable and environmental friendly. However, there are some drawbacks such as low tensile strength, modulus and flexural strength compared to industrial synthetic fibers. Various techniques have been used to increase the mechanical properties of the reinforced material in order to compete with synthetic fibers. This study is to produce reinforced fabric made from kenaf fibers woven into four different weave patterns. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…It is obviously due to the presence of more aligned fibres in the axial direction, which enabled it to hold the flexural stress developed over the surface of the material. Moreover, the satin fabric composite had a less chance for stress concentration due to lower number of interlacing points [29,31]. composites followed the same trend as obtained in the flexural and tensile testing.…”
Section: Flexural Propertiessupporting
confidence: 79%
See 1 more Smart Citation
“…It is obviously due to the presence of more aligned fibres in the axial direction, which enabled it to hold the flexural stress developed over the surface of the material. Moreover, the satin fabric composite had a less chance for stress concentration due to lower number of interlacing points [29,31]. composites followed the same trend as obtained in the flexural and tensile testing.…”
Section: Flexural Propertiessupporting
confidence: 79%
“…The jammed fabric structure has influence on the properties of the composites since in this area the resin penetration between the fibres is low. In the case of satin weave each adjacent floating yarn has a different interlacing point which makes it evenly distributed and the even yarns floating distribution with small gap makes it free for the resin to distribute evenly [29]. The highest strength values (88.06 ± 7.70 MPa) were registered for composites reinforced with hemp/PLA satin fabric, followed by hemp/PLA basket fabric and winded hemp/PLA yarn laminate.…”
Section: Composite Porositymentioning
confidence: 83%
“…It was revealed that plain fabric had higher tensile strength than twill one. This trend, even unexpected due to the high crimp of plain leading to lower mechanical properties 58 was fully reported by researchers who investigated the influence of textile properties on the tensile strength of textile 57,59,60 . After 3D printing process, the non-conductive and conductive 3D-PPOT materials have significantly higher stress at rupture when printing in the cross direction, due to more resistant monofilament used as weft yarn and increasing the weft density leading to a closer packing of the structure.…”
Section: Resultssupporting
confidence: 56%
“…However, it is different for Basket 4/4 as it decreases when it is transformed into a composite. This has already been explained in previous study as the structure of basket 4/4 changes after been process, which leads to a jammed structure and produces large empty spaces without any reinforcement [12]. The tensile modulus determines the stiffness of the composite and it is found that the strength of the woven preform is proportional to the stiffness of the composite.…”
Section: Composite Panelmentioning
confidence: 52%